Statistical Analysis for Transmission Error of Gear System with Mechanical and Thermal Deformation Uncertainties - Joon-Ho Lee; Hee-Sun Choi; Jong-Hyeon Sohn; Geun-Ho Lee; Dong-Il Park; Jin-Gyun Kim (Applied Sciences, 2021)
We establish a robust algorithm to analyze the influence of system uncertainties on the transmission error of a spur gear pair under 2D simplification. The algorithm provides a way of generating smooth cutter profiles with machining uncertainties and measuring the thermal deformation through the uncertainties in material properties. Then, it produces realizations of gear tooth profiles based on the analytical method for accuracy and computational efficiency. Numerical investigations show the statistical analysis on the tooth contact analysis by comparing steel and plastic gears. It is worthwhile remarking that the plastic gear is susceptible to the geometric error caused by thermal deformation. Moreover, although the impact of thermal deformation on steel gear may seem slim, it can have a noticeable influence when it exists with mechanical uncertainties together.